Amelia Jane gets into trouble - Blyton, Enid. (b)
One of a series of four books featuring the adventures of Amelia Jane, the doll who just can't keep out of mischief. The other toys hate her tricks, and sometimes they pay her back - for instance, by tying her to the table-leg with her own knitting, and painting her face while she's asleep.
Keywords: Dolls -- Juvenile fiction; Dolls; English fiction -- Short stories